ANALISA TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG KONSUMSI TABLET TAMBAH DARAH - Sri, Istikayati Nur; Saleh, Chusun; Nurlaila, Khairani (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
The four health problems that are considered most often experienced by adolescent girls in Indonesia are iron deficiency (anemia), short stature (stunting), chronic energy deficiency (CED), and obesity. Anemia is a body condition characterized by the results of a hemoglobin (Hb) examination in the blood that is lower than normal, which can be caused by a lack of red blood cells. Based on data from the 2023 Indonesian Health Survey (SKI), the prevalence of anemia in the 15-24 year age group was 13.2%, where women had a higher prevalence of anemia. This study aims to determine the level of knowledge of adolescent girls about consuming iron tablets. This study uses a quantitative descriptive method with a cross-sectional approach. Sampling using a total sampling technique totaling 121 respondents. Data were analyzed using univariate analysis and bivariate analysis. Bivariate analysis was carried out using chi square. The results of the study showed that the majority of respondents were aged >13-17 years, namely 78 teenage girls (64.5%), the most common source of information was obtained from the School Health Service (UKS) as many as 107 teenage girls (88.4%). Of the 121 respondents, 105 teenage girls (86.8%) had consumed Iron Tablets, and there were still quite a lot of teenage girls whose knowledge level was lacking, namely 53 teenage girls (43.8%). The description of the relationship between Information Sources and the Level of Knowledge of Teenage Girls about Consuming Iron Tablets analyzed using multiple responses and crosstabs was categorized as lacking, sufficient and good. Of the 16 teenage girls who had a low level of knowledge, 12 teenage girls (75.0%) did not consume iron tablets. There was a significant relationship between the consumption of Iron Tablets and the Level of Knowledge of teenage girls with a P value of 0.022 (p <0.05).